Provincial Citizenship: Jharkhand Domicile, Migration and Politics of Scale - Ranjan, Alok (Studies in Indian politics, 2025)
State domicile has gained prominence as a governance framework in India, as several state governments have taken protectionist policy decisions to privilege the interests of ‘residents’ against migrants. The principle operates on the two registers of politics of belonging and constitutionality and puts the construct of singular citizenship of the nation-state under strain. Primarily focusing on Jharkhand, this article studies the contentious politics of domicile as an emergence of ‘provincial citizenship’. Analytically, it rethinks the territorial assumptions of Indian citizenship and argues for studying it beyond the site of the nation-state.